The integration of water and soil based on three-in-one 3DD-P algorithm - Wang, Peipei; Liu, Xianglei; Fei, Lifan (IOP conference series. Materials Science and Engineering, 2019)
In view of the fact that geomorphic synthesis using conventional three-dimensional Douglas-Peucker algorithm leads threshold setting randomness, Complicated calculation and spatial relationship conflicts in the integrated geomorphic structure line, this paper proposes an improved 3D D-P algorithm of the indirect generalization of terrain which maintains spatial relationship consistency. Firstly, the discrete points on the water systems and the contour lines are sorted on the basis of the 3D Douglas algorithm. Then each sequence assigns a corresponding weight according to their respective characteristics, re-adjusts the position of the point, and integrates the sequence using the "three in one" idea to obtain a more comprehensive queue. Finally, the data is simplified and reconstructed according to the compression ratio to Multi-scale dynamic synthesis of terrain. The experimental results show that the method has higher accuracy in simplification, which can maintain the main topographic features of the drawing area and ensure the topological consistency between the structural lines.